PEMBAGIAN LIFE JACKET DAN EDUKASI KESELAMATAN LAUT BAGI SISWA DI DESA NUMBING - Hanum, Athiifa; Widiyani , Heni; Sihombing, Sebastian Alboen; Hanum, Atiikah; Thahira, Atikah; Adhayanto, Oksep; Suryadi, Suryadi; Arjuna, Hendra; Irman, Irman; Intan, Dian Mustika (Jurnal Abdi Insani, 2025)
The community service program entitled "Distribution of Life Jackets and Marine Safety Education for Students Using Small Boats in Numbing Village" is based on the high risks faced by students in coastal villages who use small boats as their daily means of transportation. Numbing Village, as a coastal area, has limited access to land transportation, so many students rely on small boats to go to school. However, a lack of understanding about marine safety and a lack of safety equipment, such as life jackets, increases the risk of fatal accidents at sea, especially in bad weather conditions. The main aim of this program is to improve student safety by distributing life jackets and providing marine safety education. The distribution of life jackets is expected to reduce the risk of accidents caused by drowning, while marine safety education aims to increase students' awareness and skills in maintaining personal safety while on board. Apart from that, this program also aims to build awareness of the importance of marine safety from an early age. This program involves collaboration with local schools in Numbing Village, the village government, and the local maritime community. With support from various parties, the program can run more effectively in students' daily activities. This activity is carried out through two main steps. First, the distribution of life jackets to students which has a direct impact on their physical protection when they use ships. Second, organizing marine safety education which includes explaining how to use life jackets, steps to deal with emergency situations at sea, and awareness of weather and water conditions. It is hoped that this program can be implemented in other coastal areas in Indonesia to build a better maritime safety culture.